SOCIO-PSYCHOLOGICAL PECULIARITIES OF FORMING SIBLING RELATIONSHIPS IN THE SYSTEM OF INTRAFAMILY RELATIONS (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to the scientific-methodological and theoretical analysis of social-psychological features of formation of sibling relationships in the system of intrafamily relations. The research studies of some foreign scientists concerning this problem are analyzed in the article.